2014
DOI: 10.1007/s12032-014-0093-6
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitination involved enzymes and cancer

Abstract: Ubiquitination is a post-translational modification process that regulates multiple cell functions. It also plays important roles in the development of cancer. Mechanistically, ubiquitination is a complex process that is comprised of a series of events involving ubiquitin-activating enzymes, ubiquitin-conjugating enzymes and ubiquitin ligases. In general, covalent attachment of ubiquitin to the target proteins marks them for degradation. Dysregulation of the ubiquitination process may cause carcinogenesis. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 95 publications
0
44
0
Order By: Relevance
“…Accumulating evidence has demonstrated that ubiquitination is associated with the progression of cancer [7]. There are more than 600 E3 ligases in humans, some of which regulate the expression of tumor-suppressor or tumor-promoting proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence has demonstrated that ubiquitination is associated with the progression of cancer [7]. There are more than 600 E3 ligases in humans, some of which regulate the expression of tumor-suppressor or tumor-promoting proteins.…”
Section: Introductionmentioning
confidence: 99%
“…The ubiquitination process, which includes activation by ubiquitin-activating enzymes (E1s), conjugation by ubiquitin-conjugating enzymes (E2s), and ligation by ubiquitin ligases (E3s), can alter protein interactions, location, function, activity, and lifespan. It also affects the cell cycle and regulates cancer-related processes, DNA repair, and inflammation [1, 2]. Ubiquitin-conjugating enzymes (E2s), which target proteins for degradation via the proteasome, accept ubiquitin from the E1 complex and catalyze monoubiquitination.…”
Section: Introductionmentioning
confidence: 99%
“…The functional consequences of protein ubiquitination are highly dependent on the ubiquitination pattern (monoubiquitination vs polyubiquitination) and the ubiquitination linkage types [16]. At present, eight inter-ubiquitin linkage types such as K6, K11, K27, K29, K33, K48, K63, and linear ubiquitination have been reported [17, 39, 54].…”
Section: Discussionmentioning
confidence: 99%
“…To execute the ubiquitination process, the consecutive action of three enzymes including the E1 ubiquitin-activating enzyme, the E2 ubiquitin-conjugating enzyme, and the E3 ubiquitin ligases are required for the attachment of ubiquitin to a substrate [16, 17]. The ubiquitin-proteasome system (UPS) is often utilized to fine-tune the expression of target proteins that are associated with cancer development and progression.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation